ENROFLOXACIN INDUCED OXIDATIVE STRESS AND ITS AMELIORATION WITH ANTIOXIDANTS IN LIVER HOMOGENATES OF BROILERS - A. Elamaran; P. Hariharan; S. Ramesh; S. Vairamuthu (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The experiment was conducted to evaluate the effect of enrofloxacin induced oxidative stress in liver homogenates of broiler chickens. Total fifty broiler chickens divided into five groups at the age of day 38 were used for this study. Oxidative stress was produced in the chickens with Enrofloxacin at an oral dose of 10 mg/kg b.w. In Enrofloxacin (10 mg/kg b.w) treated group, there was a  significant elevation in the oxidative biomarkers like superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), reduced glutathione (GSH) and marked increase in lipid peroxidation (MDA) of liver homogenates. Treatment with either alpha-lipoic acid (100 mg/kg b.w) or vitamin E (100 mg/kg b.w) significantly restored the antioxidant status in liver homogenates. Whereas, co-treatment of alpha-lipoic acid (100 mg/kg b.w) and vitamin E (100 mg/kg b.w) had significantly restored the antioxidant parameters which are comparable with the normal control birds. Thus the results of this study suggest that enrofloxacin induced oxidative stress in broilers at the therapeutic doses can be effectively ameliorated by treating with vitamin E and alpha-lipoic acid combination than treating with either of these drugs alone.